Digital Teaching Materials with Local Wisdom Based on Google Sites on the Topic of Plants, the Source of Life on Earth - Ni Made Dina Rahmawati; I Gede Margunayasa; I Wayan Lasmawan (Universitas Pendidikan Ganesha, 2024)
The use of digital teaching materials is minimal at the elementary school level. This research aims to create digital teaching materials based on local wisdom on Google sites, plants that are the source of life on Earth, and the learning outcomes of fourth-grade elementary school students. This type of research is RnD (Research and Development) with the ADDIE model. Data collection for this development research used questionnaire methods and test methods. Product trials are carried out by expert testers, teachers, and students. The research instruments include validity questionnaires, practicality questionnaires, and pretest and posttest results. Data analysis methods and techniques are descriptive statistical analysis and quantitative descriptive statistical analysis. Data analysis uses the t-test, namely the paired samples test. The research results were that the instrument's content validity through material experts was 95.5%, and the validity of media experts was 95.5%. Practicality is used by teachers at 97%, and practicality by students is 97.5%, so it is suitable for use. Conclusion: Digital teaching materials based on local wisdom based on Google sites developed using websites contained in Google features can be declared valid, practical, and effective in improving the learning outcomes of class IV students based on pretest and posttest data analysis. This research implies that it can improve knowledge, concepts, and theories regarding developing digital teaching materials.